Active building envelope systems toward renewable and sustainable energy. (April 2019) - Luo, Yongqiang; Zhang, Ling; Bozlar, Michael; Liu, Zhongbing; Guo, Hongshan; Meggers, Forrest
Abstract: Although passive building envelope systems dominate contemporary building design, active building envelope (ABE) research, development, and deployment are rapidly growing and present many new ways to address building energy efficiency at the façade level. This paper presents a comprehensive review on the state-of-art-research on ABEs for improving building energy efficiency. First, a clarified concept of ABE is put forward based on two conditions: The ability of lowering cooling/heating loads in buildings, and performing energy transformation as the key judging factors. Second, four major categories of ABEs, namely air-based, water-based, solid-based and kinetic façades, are discussed in terms of their system structural and functional features as well as system performance. In addition, a statistical analysis is performed for a better understanding of current research focus, general trends, as well as research methods. It is found that technical research on ABEs has dramatically increased but the ratio of ABE to general façade studies remains stable. In terms of research methods and approaches, numerical simulations are dominant. Some specific comments on limitations of current ABE studies and general suggestions for the future studies are discussed. Future work suggests the need for contributions from a wide range of scientists, engineers, and architects in the building industry and beyond to push forward building energy efficiency. Highlights: A new and effective definition of active building envelope is proposed. Research tendency, distributions and study methods offer a clear map of active building envelopes. A state-of-the-art review and discussion is presented for active building envelopes. Outlooks and recommendations for active envelopes can facilitate its further development.